Kajian Faktor-Faktor yang Berperan terhadap Literasi Keuangan Perempuan Perkotaan dalam Mendukung Percepatan Pencapaian Tujuan Pembangunan Berkelanjutan - Nurharyati Panigoro; Boby Rantow Payu; Muliyani Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the context of women, especially those living in urban areas, financial literacy plays a strategic role not only in the management of personal and family finances, but also in increasing women's participation in productive economic sectors. The purpose of this study is to analyze and identify factors that affect the level of financial literacy in urban women. The method used in this study uses a quantitative method approach. The data used in this study is in the form of primary data obtained from surveys, while data collection uses questionnaire instruments. This research is not only focused on women who have careers, but all women's groups in the city of Gorontalo. The results of the study show that the level of financial literacy of urban women in the city of Gorontalo for conventional financial products is very good and for the level of financial literacy of non-conventional products is still low. Then among the factors that have an influence on financial literacy are age, education level and income, while marital and employment status are not related to the level of financial literacy of urban women.